Surgical Treatment of Fractures of the Femoral Shaft after Total Hip Replacement - Hashiguchi, Takashi; Okudaira, Tsuyoshi; Yuge, Daishiro; Taguchi, Toshihiko; Kihune, Masao; Mimura, Hiroshi; Yamamoto, Kenji; Nakamura, Katsumi (Orthopedics & Traumatology, 1996)
This paper describes the clinical results of fractures of the femoral shaft after total hip replacement (T. H. R.). Between 1985 and 1994, we treated 7 patients, 8 femoral shaft fractures after T. H. R. Subjects included 1 male and 6 females with an average age of 60.9 years. The mean follow-up period after the final operataion was 47 months (12 months to 96 months). Treatment of the patients depended on their type of fracture. If they had no signs of loosening of the stem, we treated with osteosynthesis using a plate. It is possible to insert screws into the bone in the presence of cement and a stem. In cases with loosening of the stem, we choose to perform the revision using cementless long stem added bone grafts. At Follow-up 3-6 months after surgery, bone union was completely achieved in all of the cases and favorable clinical results were achieved.